Antioxidant capacity of water soluble extracts from Parmigiano-Reggiano cheese. (1st August 2013) - Bottesini, Chiara; Paolella, Sara; Lambertini, Francesca; Galaverna, Gianni; Tedeschi, Tullia; Dossena, Arnaldo; Marchelli, Rosangela; Sforza, Stefano
Abstract: In this work the antioxidant capacity of water soluble extracts of Parmigiano-Reggiano cheese (Water Soluble Extracts – WSEs) at different aging time was studied, by measuring their radical scavenging capacity with a standard ABTS assay. The WSEs were also fractionated by semi-preparative HPLC-UV and for each fraction the antioxidant capacity and the molecular composition was determined by LC/ESI-MS, in order to identify the most active antioxidant compounds. The antioxidant capacity was also determined after simulated in vitro gastrointestinal digestion of WSEs. The data indicated that antioxidant capacity in WSE from Parmigiano-Reggiano cheese, quite unaffected by ripening time and gastrointestinal digestion, is mostly due to free amino acids, mainly tyrosine, methionine and tryptophan, and only in minimal part to antioxidant peptides.